Does digital collective learning improve with more participants? An experiment on a collective learning platform - Orejudo, Santos; Casanova, Oscar; Cano-Escoriaza, Jacobo; Cebollero-Salinas, Ana (Frontiers in Psychology, 2025)
IntroductionThe emergence of the Internet in the educational field has opened a significant number of possibilities, including interactive “virtual spaces” of collaboration in groups of many different sizes. Based on the principles of collective intelligence, our collaborative learning platform proposes an interaction model in which participants gradually reach solutions to a problem through a series of interaction processes that culminate in a step where consensus is reached.MethodsIn our study, we compare results gathered from three groups of 11- to 12-year-old students (274, 56, and 69 participants) who dealt on the platform with a task related to emotional competencies in online environments. Large numbers of participants are possible on this platform thanks to its flexible design. Participants worked in seven phases to solve five questions with different answer formats based on a case study of social comparison on social networks.ResultsResults reveal differences in terms of evolution according to group size: the largest group achieved the best results.DiscussionWe analyzed the results through a series of variables that reveal further statistically significant differences among groups working on the same task in this novel learning environment.